1985
DOI: 10.1177/030098588502200304
|View full text |Cite
|
Sign up to set email alerts
|

Ocular Lesions of Bovine Malignant Catarrhal Fever

Abstract: Abstract. The ocular lesions of bovine malignant catarrhal fever were characterized in 15 naturally occumng and eight experimentally induced cases of the disease. Consistent findings included: lymphocytic vasculitis of retinal, scleral, posterior ciliary, and uveal vessels; uveitis, especially involving ciliary processes, ciliary body, and iris; and keratitis with corneal edema, neovascularization, and epithelial and endothelial degeneration. Lymphocytic ciliary neuritis and optic meningitis were found less fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
12
0

Year Published

1989
1989
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 13 publications
3
12
0
Order By: Relevance
“…The anterior segment abnormalities found in our study were similar to those reported in the literature 1,15–17,19,20,23,25–27,31,32,37,38,44–50,53 …”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…The anterior segment abnormalities found in our study were similar to those reported in the literature 1,15–17,19,20,23,25–27,31,32,37,38,44–50,53 …”
Section: Discussionsupporting
confidence: 91%
“…We have decided to evaluate corneal edema separately, because in cows with MCF, it is not exclusively a consequence of uveitis‐induced loss of corneal endothelial function. In one report, it was stated that peripheral corneal edema was most probably caused by MCF associated vascular and epithelial changes 37 . More importantly, we have tried to establish a practical grading scheme for corneal edema, which can be easily used by general practitioners, since it does not require any special equipment or skills, as are needed for the detection and grading of anterior uveitis.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations